2020
DOI: 10.1186/s12870-020-02590-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis at organ and time scale reveals gene regulatory networks controlling the sulfate starvation response of Solanum lycopersicum

Abstract: Background: Sulfur is a major component of biological molecules and thus an essential element for plants. Deficiency of sulfate, the main source of sulfur in soils, negatively influences plant growth and crop yield. The effect of sulfate deficiency on plants has been well characterized at the physiological, transcriptomic and metabolomic levels in Arabidopsis thaliana and a limited number of crop plants. However, we still lack a thorough understanding of the molecular mechanisms and regulatory networks underly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 108 publications
(178 reference statements)
4
16
0
Order By: Relevance
“…RNA-seq data analysis was performed as described by [ 71 ]. Briefly, sequenced reads were pseudo-aligned to the publicly available Brassica napus transcriptome obtained from Ensembl Plants using kallisto (v0.46) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…RNA-seq data analysis was performed as described by [ 71 ]. Briefly, sequenced reads were pseudo-aligned to the publicly available Brassica napus transcriptome obtained from Ensembl Plants using kallisto (v0.46) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with research into other macroelements, research on the regulation mechanisms of S assimilation and absorption in plants is lagging behind, and is still poorly understood [ 65 , 66 ]. In recent years, with the development of genomic, transcriptomic, and metabolomic research, understanding of the physiological and molecular regulatory mechanisms underlying responses to S-deficiency stress in plants has been enhanced [ 5 , 6 , 30 , 65 , 67 , 68 , 69 ].…”
Section: Molecular Regulatory Mechanisms Of S Absorption and Assimmentioning
confidence: 99%
“…Similar approaches focusing on S deficiency have shown that among the 632 DEGs in S-deprived plants, most were related to the sulfur assimilation pathway but also to the flavonoid, auxin, and jasmonate biosynthetic pathways [ 29 ]. Other authors have demonstrated that variations in sulfur availability modulates the expression of genes involved in the regulation of S, N, and P metabolisms [ 30 , 31 , 32 ], highlighting the strong interactions between S and other elements. Previously, it has been reported that K deficiency modulates the expression of a smaller panel of genes than N or P deficiencies [ 33 ].…”
Section: Introductionmentioning
confidence: 99%